Medical and Paramedical Care of Patients With Cerebellar Ataxia During the COVID-19 Outbreak: Seven Practical Recommendations of the COVID 19 Cerebellum Task Force - Manto, Mario; Dupre, Nicolas; Hadjivassiliou, Marios; Louis, Elan D.; Mitoma, Hiroshi; Molinari, Marco; Shaikh, Aasef G.; Soong, Bing-Wen; Strupp, Michael; Van Overwalle, Frank; Schmahmann, Jeremy D. (Frontiers in Neurology, 2020)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV2), the cause of current coronavirus disease 2019 (COVID-19), primarily targets the respiratory system. Some patients also experience neurologic signs and symptoms ranging from anosmia, ageusia, headache, nausea and vomiting to confusion, encephalitis and stroke. Approximately 36% of those with severe COVID-19 experience neurological complications. The virus may enter the central nervous system through the olfactory nerve in the nasal cavity and damage neurons in the brainstem nuclei involved in the regulation of respiration. Patients with cerebellar ataxia (CA) are particularly vulnerable to severe outcome if they contract COVID-19 because of the complexity of their disease, the presence of comorbidities, and their use of immunosuppressive therapies. Most CA patients burdened by progressive neurologic deficits have substantially impaired mobility and other essential functions for which they rely heavily on ambulatory services including rehabilitation and psychosocial care. Cessation of these interventions because of isolation restrictions places the CA patient population at risk of further deterioration. This international panel of ataxia experts provides recommendations for neurologists caring for CA patients, emphasizing a pro-active approach designed to maintain their autonomy and well-being: continue long-term medications, promote rehabilitation efforts, utilise the technology of virtual visits for regular contact with health care providers, and pay attention to emotional/psychosocial health. Neurologists should play an active role in decision-making in those CA cases requiring escalation to intensive care and resuscitation. Multi-disciplinary collaboration between care teams is always important, and never more so than in the context of the current pandemic.